Ampere-level co-electrosynthesis of formate from CO2 reduction paired with formaldehyde dehydrogenation reactions - Zhengyuan Li; Peng Wang; Guanqun Han; Shize Yang; Soumyabrata Roy; Shuting Xiang; Juan D. Jimenez; Vamsi Krishna Reddy Kondapalli; Xiang Lyu; Jianlin Li; Alexey Serov; Ruizhi Li; et al. (Nature Communications)
Abstract Current catalysts face challenges with low formate selectivity at high current densities during the CO2 electroreduction. Here, we showcase a versatile strategy to enhance the formate production on p-block metal-based catalysts by incorporating noble metal atoms on their surface, refining oxygen affinity, and tuning adsorption of the critical oxygen-bound *OCHO intermediate. The formate yield is observed to afford a volcano-like dependence on the *OCHO binding strength across a series of modified catalysts. The rhodium-dispersed indium oxide (Rh/In2O3) catalyst exhibits impressive performances, achieving Faradaic efficiencies (FEs) of formate exceeding 90% across a broad current density range of 0.20 to 1.21 A cm−2. In situ Raman spectroscopy and theoretical calculations reveal that the oxophilic Rh site facilitates *OCHO formation by optimizing its adsorption energy, placing Rh/In2O3 near the volcano-shaped apex. A bipolar electrosynthesis system, coupling the CO2 reduction at the cathode with the formaldehyde oxidative dehydrogenation at the anode, further boosts the FE of formate to nearly 190% with pure hydrogen generation under an ampere-level current density and a low cell voltage of 2.5 V in a membrane electrode assembly cell.